Binocular dynamic visual acuity in dry eye disease patients - Ren, Xiaotong; Wang, Yuexin; Wu, Tingyi; Jing, Dalan; Li, Xuemin (Frontiers in Neuroscience, 2023)
Purpose: To investigate binocular dynamic visual acuity (DVA) for patients with dry eye disease (DED). Methods: The prospective study included DED patients. The binocular DVA at 40 and 80 degrees per second (dps), Ocular Surface Disease Index (OSDI), tear meniscus height (TMH), tear film break-up time first (TBUTF), corneal fluorescein staining (CFS), eyelid margin abnormalities and meibomian gland (MG) abnormalities morphology and function were evaluated. A deep learning model was applied to quantify the MG area proportion. The correlation between DVA and DED parameters was analyzed. Results: A total of 73 DED patients were enrolled. The age, OSDI, CFS, MG expressibility, secretion quality, and eyelid margin abnormalities were significantly positively correlated with the DVA for 40 and 80 dps (all P<0.05). The MG area proportion in the upper eyelid was negatively correlated with DVA at 40 dps (R = -0.293, P<0.001) and at 80 dps (R= -0.304, P<0.001). Subgroup analysis by MG grade demonstrated that the DVA of patients with severe MG dropout (<25% of the total area) was significantly worse than other mild and moderate groups, both in 40 and 80dps (all P<0.05). The patients with CFS showed worse 40 (P<0.001) and 80 dps (P<0.001) DVA than the patients without CFS. Conclusion: Binocular DVA is significantly associated with DED symptoms and signs. The DED patients with CFS and severe MG dropout and dysfunction have worse DVA.